Recent Advances of Activatable Molecular Probes Based on Semiconducting Polymer Nanoparticles in Sensing and Imaging. Issue 6 (9th February 2017) - Lyu, Yan; Pu, Kanyi
Abstract : Molecular probes that change their signals in response to the target of interest have a critical role in fundamental biology and medicine. Semiconducting polymer nanoparticles (SPNs) have recently emerged as a new generation of purely organic photonic nanoagents with desirable properties for biological applications. In particular, tunable optical properties of SPNs allow them to be developed into photoluminescence, chemiluminescence, and photoacoustic probes, wherein SPNs usually serve as the energy donor and internal reference for luminescence and photoacoustic probes, respectively. Moreover, facile surface modification and intraparticle engineering provide the versatility to make them responsive to various biologically and pathologically important substances and indexes including small‐molecule mediators, proteins, pH and temperature. This article focuses on recent advances in the development of SPN‐based activatable molecular probes for sensing and imaging. The designs and applications of these probes are discussed in details, and the present challenges to further advance them into life science are also analyzed. Abstract : Semiconducting polymer nanoparticles (SPNs) have shown great promise in life science. Recent advances of developing SPNs into smart activatable probes for biological sensing and molecular imaging are discussed.